Experiences of virtual teaching during COVID-19 in medical institutes of Karachi, Pakistan: teachers’ perspective - Syeda Rubaba Azim; Nisar, Munizha; Baig, Mukhtiar; Azfar, Syed Muhammad; Azim, Syeda Nazish; Anwar, Adina (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the experiences of faculty members related to virtual teaching. Method: The cross-sectional study was conducted from January 15 to March 15, 2021, at undergraduate medical institutions located in Karachi, and comprised all the faculty members. Data was collected using a Google Survey questionnaire, and it was analysed using SPSS 20. Results: Of the 385 subjects, 157(40.78%) were from basic sciences faculty, and 228(59.2%) were from the clinical sciences faculty. The majority had 3-5 years of teaching experience 142(37%). The most common online tool was Zoom 250 250(65%). The faculty who had prior experience or had received formal training for online teaching was more successful in controlling and engaging students than the rest (p<0.001). Those who had enough computer literacy had a better experience in conducting online teaching sessions (p=0.01). The experienced faculty found the opportunity to focus more on the topic that was to be taught online (p<0.001). Conclusion: Most of the faculty members used online tool Zoom. Faculty members with computer literacy and proper training for online teaching were more successful in controlling and engaging students and conducting online teaching sessions. Key Words: Virtual teaching, Zoom, Student engagement, Motivation, Computer literacy, Faculty development.